Supplementation with Omega-3 fatty acids in the supportive treatment of depression - systematic review - Karolina Chmielarz; Magdalena Zapała; Adrian Hunek; Karolina Kaziród; Joanna Wiśniewska-Skomra; Kinga Tylutka; Anna Hapon (Kazimierz Wielki University, 2023)
Omega-3 is a polyunsaturated fatty acid (PUFA) with a double bond present at the ω-3 carbon atom. Recently, many neurobiologists and psychiatrists have been studying the involvement of inflammatory factors and mechanisms in the pathogenesis of depression, including factors like an improper diet with an excess of omega-6, gut dysbiosis, obesity, and autoimmune diseases. The present study focuses on the impact of unsaturated fatty acids on mood improvement and cognitive processes in elderly patients with major depressive disorder (MDD) resistant to standard treatment. This form of depression is often associated with autoimmune diseases, including rheumatoid arthritis (RA), systemic lupus erythematosus, and inflammatory bowel diseases. The influence of omega-3 supplementation on depression prevention and its effects on childhood depression were also examined. It should be noted that some publications do not confirm the antidepressant effects of omega-3. However, this article provides evidence of the supportive role of omega-3 in depression treatment, based on neuroendocrine, metabolic, and immunological reactions. Objective: Literature review on the impact of omega-3 on depression treatment, considering its forms, inflammatory mechanisms, neuroendocrine factors, diet, lifestyle, and age. Materials and Methods: Literature review based on available sources from PubMed and Google Scholar. Conclusions: Omega-3 is a polyunsaturated fatty acid that positively affects the functioning of the body. Many research studies confirm its antidepressant and anti-inflammatory effects, making it a potential adjunctive treatment for depression, especially in elderly patients with major treatment-resistant depression (MDD) coexisting with other chronic diseases. The results of studies on the relationship between omega-3 and antidepressant action also depend on various environmental factors and lifestyle choices.